Aplikasi Virtual Reality Media Pembelajaran Sistem Tata Surya - Prayudha, I Putu Astya; Wiranatha, Anak Agung Ketut Agung Cahyawan; Raharja, I Made Sunia (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 5, No. 2 Agustus 2017, 2017)
Learning of the solar system is taught since primary school. The learning materials of the solar system are generally explained through blackboards and using books, causing a less of visualization of the solar system that becomes an obstacle in the learning process of the solar system. Develop Virtual Reality Application Learning Media of Solar System in this study aims to facilitate learning with the addition of visualization of the delivery of materials related to the solar system. The application is designed to combine entertainment and knowledge where users interact with virtual environments and see the existence of planets and planets information in the solar system with virtually mode. Application are developed with the delivery of text and voice learning to provide knowledge to users such as the distance the planet to the Sun, diameter, layers, and the constituents of the planet. Users agree Virtual Reality Application Learning Media of Solar System effectively facilitate learning related to the solar system system as evidenced by the questionnaire of 60% for agree value on the content aspect.